Inventário para a Memória da Indústria Gráfica em Pelotas-RS (1920). - Leschko, Nadia Miranda (2011)
This paper aims to contribute to the formation of a graphics memory to support taking the inventory as a means of printing industry in Pelotas / RS / Brazil in the 1920's, this consisting of companies operating in the merge of graphic designs. Pelotas was chosen as an area of concentration of research in view of its historical background and studies conducted in the area of memory. The focus is temporal bounding the 1920 s on the basis of regional importance that the city obtained as a major producer of culture and information. The research took place at the Pelotas Public Library as source reviewed journals and graphic works produced at the time. The structure of the work consists of the first chapter containing historical charts of the processes, the second chapter contains the methodology, data from field research and inventory summary of the companies operating the decade and the third chapter related data from previous chapters and an analytical inventory of the printing industry in Pelotas - RS